Hubungan Kualitas Dashboard Manajemen Rumah Sakit Dengan Kecepatan Pengambilan Keputusan Manajerial Pada Rumah Sakit Islam Malahayati Medan Tahun 2026 - Diah Karlina (STIKES Columbia Asia Medan, 2026)
The rapid digital transformation of Indonesian hospitals has positioned management dashboards as strategic instruments to support evidence-based managerial decision-making. However, the extent to which the quality of hospital management dashboards influences the speed of managerial decision-making has not been sufficiently examined in Indonesian tertiary hospitals. This study aimed to analyze the relationship between the quality of the hospital management dashboard and the speed of managerial decision-making at Malahayati Islamic Hospital Medan in 2026. A quantitative analytical study with a cross-sectional design was conducted on 70 managerial staff (heads of units, heads of installations, supervisors, head nurses, and managers) selected through simple random sampling from a population of 85. Data were collected using a validated Likert-scale questionnaire (1–5) covering six dimensions of dashboard quality and four dimensions of managerial decision-making speed. Univariate, bivariate (Spearman's rank correlation), and simple linear regression analyses were performed. The results showed that 68.6% of respondents perceived the dashboard quality as good and 71.4% reported fast managerial decision-making. A significant, strong, and positive correlation was found between dashboard quality and managerial decision-making speed (r = 0.782; p < 0.001), with an R² of 0.612. The study concludes that improving dashboard quality substantially accelerates managerial decisions, supporting the DeLone & McLean Information System Success Model in the Indonesian hospital context.